Machining of Two-Dimensional Sinusoidal Defects on Ignition-Type Capsules to Study Hydrodynamic Instability at the National Ignition Facility. (1st September 2016) - Giraldez, E. M.; Hoppe, M. L.; Hoover, D. E.; Nguyen, A. Q. L.; Rice, N. G.; Garcia, A. M.; Huang, H.; Mauldin, M. P.; Farrell, M. P.; Nikroo, A.; Smalyuk, V.
Abstract: Hydrodynamic instability growth and its effects on capsule implosion performance are being studied at the National Ignition Facility (NIF). Experimental results have shown that low-mode instabilities are the primary culprit for yield degradation. Ignition-type capsules with machined two-dimensional (2-D) sinusoidal defects were used to measure low-mode hydrodynamic instability growth in the acceleration phase of the capsule implosion. The capsules were imploded using ignition-relevant laser pulses and the ablation-front modulation growth was measured using X-ray radiography. The experimentally measured growth was in good agreement with simulations. Fabrication of the preimposed 2-D sinusoidal defects of different wavelengths and amplitudes on the surfaces of ignition-type capsules was accomplished by General Atomics leading up to and during the Hydro-Growth Radiography campaign for the hydrodynamic instability growth experiments conducted at NIF between 2013 and 2014. The 2-D sinusoidal defects were imposed on ignition-type capsules by machining the surface of the capsule. The fabrication trials showed that there are six parameters that can affect the ripple form, wall thickness, and the extent of the pattern about the equator of the capsule: (1) knowing accurately the outer diameter of the capsule, (2) the roundness of the capsule (modal content), (3) the cutting tool alignment with respect to the surface of the capsule, (4) the radius and form of the cutting tool, (5) tool touch-off, and (6) the runout of the capsule center with respect to the axis of rotation of the lathe's spindle. In this paper, we will describe the importance of these parameters on the machining of uniform 2-D sinusoidal defects.